Endovascular treatment of an unruptured ophthalmic artery aneurysm with a flow diverter: a case report (Faculty of Medicine Universitas Indonesia, 2021)
An unruptured aneurysm is often asymptomatic or present without neurological deficits, causing severe morbidity. However, the potential of this defect to rupture requires proper management. Herein, we report a case of an unruptured saccular aneurysm of the ophthalmic artery with initial clinical seizures. The patient was treated by flow diversion which redirects the blood flow that normally leads to the protrusion of the aneurysm back to the main vessel. Flow diversion is chosen because it is less risky and has a faster recovery time than other treatment options, but it is more expensive than others. Although this technology is not new, there is no report on its implementation in Indonesia. The patient was prescribed antiplatelet treatment for at least 6 months post-treatment, then she showed no sign of seizure or new focal neurological deficits 4 months post-treatment. The patients were expected to undergo digital subtraction angiography evaluation 6 months after flow diversion treatment, but it has not been performed due to the coronavirus disease 2019 pandemic.